An Ancient Molecular Arms Race: Chlamydia vs. Membrane Attack Complex/Perforin (MACPF) Domain Proteins - Keb, Gabrielle; Fields, Kenneth A. (Frontiers in Immunology, 2020)
Dynamic interactions that govern the balance between host and pathogen determine the outcome of infection and are shaped by evolutionary pressures. Eukaryotic hosts have evolved elaborate and formidable defense mechanisms that provide the basis for innate and adaptive immunity. Proteins containing a membrane attack complex/Perforin (MACPF) domain represent an important class of immune effectors. These pore-forming proteins induce cell killing by targeting microbial or host membranes. Intracellular bacteria can be shielded from MACPF-mediated killing, and Chlamydia spp. represent a successful paradigm of obligate intracellular parasitism. Ancestors of present-day Chlamydia likely originated at evolutionary times that correlated with or preceded many host defense pathways. We discuss the current knowledge regarding how chlamydiae interact with the MACPF proteins Complement C9, Perforin-1, and Perforin-2. Current evidence indicates a degree of resistance by Chlamydia to MACPF effector mechanisms. In fact, chlamydiae have acquired and adapted their own MACPF-domain protein to facilitate infection.